2021
DOI: 10.3390/ijerph18105186
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Exposure across Latino Ethnicities

Abstract: The Hispanic/Latino health paradox is the well-known health advantage seen across the Hispanic/Latino racial category in the US. However, this racial category collapses several distinct ethnic groups with varying spatial distributions. Certain populations, such as Dominicans and Cubans, are concentrated in specific areas, compared to more dispersed groups such as Mexicans. Historical peculiarities have brought these populations into contact with specific types of environmental exposures. This paper takes a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Another study using 2015 data from a different exposure prediction model also found that U.S. Census tract immigrant percentage was associated with higher exposures. 63 In a smaller setting using Texas school districts, a similar analysis found county-level immigrant children proportion was positively associated with higher nitrogen dioxide ( ) levels. 58 …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study using 2015 data from a different exposure prediction model also found that U.S. Census tract immigrant percentage was associated with higher exposures. 63 In a smaller setting using Texas school districts, a similar analysis found county-level immigrant children proportion was positively associated with higher nitrogen dioxide ( ) levels. 58 …”
Section: Resultsmentioning
confidence: 92%
“…In the United States, there was a range of small area-level studies and large regional studies with individual data that found disparities in exposures to monitored black carbon (BC) 72 and ozone ( ), 68 as well as model-predicted fine particulate matter ( ) 61 , 63 , 65 , 73 and hazardous air pollutants (HAPs). 57 , 66 , 67 , 69 HAPs are 187 toxic air chemicals, including benzene, perchloroethylene, and methylene chloride, on a list maintained through the U.S. Environmental Protection Agency’s (EPA) 2011 National Air Toxics Assessment.…”
Section: Resultsmentioning
confidence: 99%